Pengaruh Pendidikan, Umur, Jenis Kelamin, Lama Usaha, Modal Dan Pendapatan Terhadap Mobilitas Usaha Pedagang Kaki Lima Di Handil Bakti Kabupaten Barito Kuala - Rizki Agustina; Ahmad Yunani (PPJP Universitas Lambung Mangkurat, 2020)
This research aims to know and analyze how much influence education, age, gender, length of business, capital, and income to Business street vendors' mobility in Handil Bakti regency of Barito Kuala. The method used in this research is the quantitative method, with the education variable, age, gender, length of effort, capital and income to the mobility business of the street vendors in Handil Bakti regency of Barito Kuala, data used Coeseoner primary and interviews with data 58 respondents and data analysis techniques using Binary logistic regression. The results of this study showed that the length of business has a partial influence on the mobility of company of the street vendors in Handil Bakti District Barito Kuala; education, age, gender, capital, and income are simultaneously influential to The mobility of business of the street vendors in Handil Bakti of Barito Kuala District and variables that are the dominant influence on the mobility of company of the street vendors in Handil Bakti District Barito Kuala is the old business